como resolver passo a passo ²√4*²√3÷²√3+4²*4³÷25

1
²√4*²√3/²√3 + 4² * 4³/25 =
²√12/²√3 + 42+3/25 =
²√12*²√3 / ²√3*²√3 + 45/25 =
²√36/3 + 1024/25 =
6/3 + 1024/25 =
2 +1024/25 +
(50+1024)/25 =
1074/25
Cola no world que a letra fica maior
²√4*²√3/²√3 + 4² * 4³/25 =
²√12/²√3 + 42+3/25 =
²√12*²√3 / ²√3*²√3 + 45/25 =
²√36/3 + 1024/25 =
6/3 + 1024/25 =
2 +1024/25 =
(50+1024)/25 =
1074/25

Respostas

2013-08-29T21:58:49-03:00
²√4*²√3/²√3  +  4² * 4³/25  =      ²√12/²√3  +  42+3/25 =        ²√12*²√3 / ²√3*²√3  +  45/25 =            ²√36/3  +  1024/25 =           6/3  +  1024/25 =           2  +1024/25 +(50+1024)/25  =             1074/25